Bridging the gap between conceptualisation & assessment of intercultural competence - Almeida, Joana Filipa Cardoso Lopes de
This paper aims at deconstructing the intercultural competence assessment task by building a coherent framework to assess the IC of incoming Campus Europae students at the University of Aveiro in 2011/12. Our discussion focuses on pre/post-test design survey techniques, by reflecting upon the process of moving from the first to the improved final version